Bio-inspired smart electronic-skin based on inorganic perovskite nanoplates for application in photomemories and mechanoreceptors. Issue 1 (17th December 2020) - Xu, Zhongwei; Wu, Chaoxing; Zhu, Yangbin; Ju, Songman; Ma, Fumin; Guo, Tailiang; Li, Fushan; Kim, Tae Whan
Abstract : The development of artificial skin, such as electronic skin, is critical to emerging artificial intelligence systems. Abstract : The development of artificial skin, such as electronic skin, is critical to emerging artificial intelligence systems. Electronic skins reported to date are mechanically flexible, and can detect various stimuli, but lack the ability to regulate themselves and learn information from the outside world. The integration of bio-inspired multifunction in a single electronic platform is critical to the development of e-skin systems. Here, we demonstrate a self-powered, light-stimulated, smart e-skin based on a photosensitive perovskite material. The electronic skin implements the functions of both tactile sensing and photoelectric neural computing. The strategy for developing such a material system and architecture of the electronic skin meets the requirement of multifunctional smart human–machine interfaces and has promising potential for application in future artificial intelligence systems.